2009
DOI: 10.1098/rsif.2009.0133
|View full text |Cite
|
Sign up to set email alerts
|

Rate-dependent frictional adhesion in natural and synthetic gecko setae

Abstract: Geckos owe their remarkable stickiness to millions of dry, hard setae on their toes. In this study, we discovered that gecko setae stick more strongly the faster they slide, and do not wear out after 30 000 cycles. This is surprising because friction between dry, hard, macroscopic materials typically decreases at the onset of sliding, and as velocity increases, friction continues to decrease because of a reduction in the number of interfacial contacts, due in part to wear. Gecko setae did not exhibit the decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 89 publications
(210 reference statements)
5
112
2
Order By: Relevance
“…These adhesives showed reusability out to 30 000 trials, which matches favourably with the performance of geckos [39], demonstrated a strong directional preference and were successfully deployed on a climbing robot [40].…”
Section: Directional Dry Adhesivesmentioning
confidence: 73%
“…These adhesives showed reusability out to 30 000 trials, which matches favourably with the performance of geckos [39], demonstrated a strong directional preference and were successfully deployed on a climbing robot [40].…”
Section: Directional Dry Adhesivesmentioning
confidence: 73%
“…Adult G. viridula slid continuously when centrifuged, suggesting either an aquaplaning-like effect [64] or stick-and-slip reduction owing to the presence of multiple minute contacts instead of one or few larger ones [65,66]. Owing to multiple minute contacts, stickand-slip events happen at each single contact, but at different times.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to sawfly larvae [58] and adult codling moths [7], beetle larvae did not slide continuously: they rather stayed at the same position until they suddenly lost contact at certain critical centrifugal force. While hairy pads [66] or sheet-like aroliae [64] start slipping when lateral forces are applied, round larval pads are more likely to tilt and roll. This would lead to sudden detachment, when the muscle strength, required for keeping the leg in position, is surpassed by centrifugal force.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the friction behaviour of these microfibril arrays has been investigated by different research groups (e.g. Majidi et al 2006;Bhushan & Sayer 2007;Kim et al 2007;Varenberg & Gorb 2007;Yao et al 2007;Shen et al 2008Shen et al , 2009Gravish et al 2009;Vajpayee et al 2009). In this work, we focus on synthetic bioinspired surfaces instead of fibrillar structures in small animals such as gecko.…”
Section: Introductionmentioning
confidence: 99%